Gamma ray‐induced glial activation and neuronal loss occur before the delayed onset of brain necrosis. Issue 10 (26th August 2020) - He, Baixuan; Wang, Xia; He, Yong; Li, Honghong; Yang, Yuhua; Shi, Zhongshan; Liu, Qiang; Wu, Minyi; Sun, Haohui; Xie, Jiatian; Zhang, Zhan; Yu, Pei; et al.
Abstract: Radiotherapy is one of the most effective treatments for head and neck tumors. However, delayed radiation‐induced brain necrosis (RN) remains a serious issue due to the lack of satisfying prevention and effective treatment. The pathological role of radiation in the delayed onset of brain necrosis is still largely unknown, and the traditional animal model of whole brain irradiation, although being widely used, does not produce reliable and localized brain necrosis mimicking clinical features of RN. In this study, we demonstrated a successful RN mouse model using optimized gamma knife irradiation in male C57BL/6 mice. On the premise that brain necrosis started to appear at 6 weeks postirradiation in our RN model, as confirmed by both MRI and histopathological examinations, we systematically examined different time points before the onset of RN for the histopathological changes and biochemical indicators. Our initial results demonstrated that in the ipsilateral hemisphere of the irradiated brains, a significant decrease in neuronal numbers that occurred at 4 weeks and a sustained increase in TNF‐α, iNOS, and other inflammatory cytokines beginning at 1‐week postirradiation. Changes of cell morphology and cell numbers of both microglia and astrocytes occurred as early as 1‐week postirradiation, and intervention by bevacizumab administration resulted in reduced microglia activation and reduction of radiation‐induced lesion volume, indicating that chronic glial activation may result in subsequent elevation of inflammatory factors, which led to the delayed onset of neuronal loss and brain necrosis. Since C57BL/6 is the most widely used strain of genetic engineered mouse model, our data provide an invaluable platform for the mechanistic study of RN pathogenesis, identification of potential imaging and biological biomarkers, and the development of therapeutic treatment for the disease.